Hirschsprung's Disease and Congenital Deafness. Issue 4 (December 1973) - Skinner, Rosalind; Irvine, David
Abstract : An association of Hirschsprung's disease (congenital intestinal aganglionosis) and profound congenital deafness is described in four unrelated patients and another reported case which was found in the literature. It is suggested that this might represent a new syndrome.